Using System Dynamics to Simulate the Management of Operation and Maintenance of Ship Machinery under the Port Availability Constraints - Dhimas Widhi Handani; Makoto Uchida (International Journal of Supply Chain Management, 2013)
The total cost of ship machinery operation (CT) must be kept at the minimum value while considering the safety from failure. This paper proposes a model to minimize the CT by endeavouring the value of minimum Reliability Index (RI) of the machinery. The minimum RI is the level of reliability of machinery where we need to take maintenance action after some period of operation time. The alteration of minimum RI causes the changes of the composition of CT, including running cost (Cr), maintenance cost (Cm) and downtime cost (Cd). This paper discusses the operation of pumps which are installed in the cooling system of main engine of ship. As constraint, the maintenance of the pumps is assumed only possible to be carried out in the particular available port. This study utilizes the System Dynamics (SD) to construct two kinds of proposed models of machinery operation. They are model 1, without forecasting and model 2, with forecasting of minimum RI. Model 1 results in minimum CT, while model 2 reaches a CT lower than the outcome of model 1.